1986
DOI: 10.1021/ic00224a026
|View full text |Cite
|
Sign up to set email alerts
|

Redox reactivity of photogenerated pentacarbonylchromium species: formation of [Cr(III)(o-semiquinone)3] complexes

Abstract: The metal hyperfine parameters \AZ\ = 645 X 10"4 cm"1 and \ ^\ = 697 X 10"4 cm"1 of the CuF2 molecule17 are almost isotropic and far higher than those of K2Zn[Cu]F4, or almost all other copper(II) complexes, clearly implying a significant unpaired spin density in the copper 4s orbital. The gxy value of 2.601 suggests an orbital contribution µ = 0.112 for CuF2, yielding "best fit" estimates of the hyperfine constants Az = 684 X 10"4 cm"1 and Axy = 657 X 10"4 cm"1 using a value of K = -1.5. This implies an occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 4 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Their synthetic route involves a redox reaction between a Cr II starting material (Cr(CTH)Cl 2 ) and the parent quinone. The approach is similar to that used for forming tris-semiquinone complexes, e.g., Cr 0 plus 3 equiv of quinone to yield a Cr(SQ) 3 complex. , An advantage of this synthetic strategy is the lability of the Cr II synthon toward loss of the chloride ligands. However, chromatographic work revealed that in our hands several other products are also formed in this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Their synthetic route involves a redox reaction between a Cr II starting material (Cr(CTH)Cl 2 ) and the parent quinone. The approach is similar to that used for forming tris-semiquinone complexes, e.g., Cr 0 plus 3 equiv of quinone to yield a Cr(SQ) 3 complex. , An advantage of this synthetic strategy is the lability of the Cr II synthon toward loss of the chloride ligands. However, chromatographic work revealed that in our hands several other products are also formed in this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Since no chemical and spectroscopic studies of Cr III (SQ) 3 in polar solvents have yet been reported, the electronic absorption spectra of Cr III (Cl 4 SQ) 3 were determined in dichloromethane,5a carbon disulfide, cyclohexane, nitromethane, acetone, and benzonitrile to investigate the conversion of Cr III (X 4 SQ) 3 to 1 − 6 . As shown in Figure (top), the spectra obtained for the solvents with a low dielectric constant (ε r at 293 K), cyclohexane (ε r = 2.02), carbon disulfide (ε r = 2.64), and dichloromethane (ε r = 9.02), were found to be similar to each other.…”
Section: Resultsmentioning
confidence: 99%